A review: crystal growth for high-performance all-inorganic perovskite solar cells - Chen, Weijie; Li, Xinqi; Li, Yaowen; Li, Yongfang (Energy & environmental science, 2020)
Recently, halide perovskites have become one of the most promising materials for solar cells owing to their outstanding photoelectric performance. Among them, metal halide all-inorganic perovskites (CsPbX 3 ; where X denotes a halogen) show superior thermal and light stability. In particular, the power conversion efficiency (PCE) of perovskite solar cells (pero-SCs) based on a CsPbX 3 active layer has shown a steady increase from 2.7% to 19.03% with the improvement of the CsPbX 3 crystal quality. In this review, we summarize methodologies that have been employed for controlling the growth of all-inorganic perovskite films so far, including precursor solution deposition, substrate modification, composition doping, and surface engineering. Furthermore, we discuss the effect of the perovskite crystal characteristics on defects and the perovskite film morphology, both of which are closely related to device performance. Finally, conclusions and perspectives are presented along with useful guidelines for developing all-inorganic pero-SCs with high PCE and robust stability. The key factors for high-quality all-inorganic perovskite crystal growth.